Authority of the Executive Board in Appointing Acting Substitutes for Regional Heads in a Presidential Government System According to the 1945 Constitution of the Republic of Indonesia - Bakhri, M Said (Journal of Law and Social Politics, 2023)
In 2023 there are 17 governors, 38 mayors and 115 regents vacant, 2 year vacancy, limited authority (running programs are constrained), Echelon 1, TNI and Polri officials are active in concurrent positions, sociology issues do not involve the community. This writing is about the position of the executive branch in appointing Acting Regional Heads in the 2024 simultaneous elections, and determining the mechanism for appointing Government Officials in accordance with Pancasila and the 1945 Constitution of the Republic of Indonesia. The conclusion of this writing is that the appointment of Regional Heads of the executive branch creates a shift in the ideology of the four Pancasila precepts, and a shift in the interpretation of the executive branch of the Article 18 paragraph (4) of the 1945 Constitution of the Republic of Indonesia, as well as Law no. 23 of 2014. The mechanism for appointing government officials according to Pancasila and the 1945 Constitution of the Republic of Indonesia, is a by-election which is the format of the theory of people's sovereignty, participatory democracy, representative democracy, tricameral system, and Law no. 23 of 2014. The first writing recommendation is that the President approves a Presidential Regulation concerning the implementation of Law no. 6 of 2020, because the span of control from the President was handed down to the Ministry of Home Affairs to determine Regional Heads. The second recommendation involves the General Election Commission, DPRD, and customary institutions registered with the National Unity and Political Agency of the Ministry of Home Affairs. This is in accordance with Law no. 1 of 2014 and Law no. 17 of 2014 the authority of the legislature to monitor the law.